Caracterización de parásitos gastrointestinales en cerdos de traspatio y su correspondiente prevención y control en el cantón de Latacunga. - Muñoz Guaico, Veronica Alexandra (2022)
The exploration was done at rural parishes of Latacunga canton, Cotopaxi province with goal to characterize gastrointestinal parasites on backyard pigs, qualitative technique was used, through probabilistic examining, in a basic irregular way, which 100 pigs were tested among males and females separated into gatherings of 10 creatures for each parish, the fecal example was taken from pigs to be analyzed through flotation strategy - "Sheather Sugar". Through acquired outcomes in Latacunga canton, next parasites were distinguished: "Hyostrongylus rubidus, Oesphagostomun demtaum, Ascaris suum, Balantidium coli and Trichuris suis". At rural engaged parishes with researched task, the most susceptible age to parasitosis is 5-8 months with a high predominance at Hyostrongylus rubidus with 51%. As per sex, the presence of Hyostrongylus rubidus was recognized in two females (30%) and males (24%), a proposal for a prevention protocol and parasites control in backyard pigs was developed. Concluding that in Latacunga canton, 71% of the backyard pigs presented gastrointestinal parasitosis.